The Role of the Teacher in Forming the Religious Character of Students in Islamic Religion Subjects at MTs Plus Labuhan - Dilah Arsitah; Nadia Khairina; Mhd Iqbal Hussein (Yayasan Rahmat Islamiyah, 2023)
The purpose of this research is to find out the concept of implementing the role of the PAI teacher in the formation of religious character, to describe the role of the PAI teacher in the formation of the religious character of students, this research uses a qualitative approach. Methods of collecting interview data and documentation sourced from secondary data. The results of the study 1) the role of the PAI teacher in shaping student character through classical, 2) the exemplary displayed by the PAI teacher through attitudes in the learning process, supervision, direction and motivation of the service process. The conclusion of this study is that the teacher's role in cultivating religious character has been maximized by using the role of educator as well as teaching by taking the time.